Application of multi-mode joint teaching method in the integrated Traditional Chinese and western medicine nursing ward round for a patient with thyroid disease (“三轨”联合教学模式在1例石瘿患者中西医结合护理临床教学查房中的应用) - LIU Ai (刘爱); TONG Lu (佟璐); FENG Ying (冯莹); DU Yun (杜云); LI Jie (李解); LI Siyuan (李思远); YAN Hong (颜红) (中西医结合护理, 2023)
In this paper, a combination of Problem-based Learning (PBL), Case-based Learning(CBL)and Flipped Classroom was used to conduct teaching ward round of nursing for a patient with thyroid disease. Taking the clinical teaching round of a patient with stony goiter as an example, this paper explored the transformation from the conventional clinical teaching method of nursing to the comprehensive application of multi-mode joint of clinical teaching. Focusing on the nursing students, the multi-mode joint model was a problem-oriented and case-based approach. It constructed a new type of teaching ward round of integrated traditional Chinese and western medicine nursing by taking clinical thinking ability as motif, disease related knowledge as the support, and teacher-student and nurse-patient interaction as means. It provides theoretical and practical basis for comprehensively improving the quality of nursing work, teaching quality and patient satisfaction, and exploring the cultivation of high-quality comprehensive Traditional Chinese Medicine nursing talents. (本文探讨运用以问题为基础学习(PBL)、以案例为基础学习(CBL)和翻转课堂的“三轨”联合教学进行护理教学查房的效果。以普外科1例石瘿患者的临床教学查房为例, 探索从传统单一的护理临床教学方法向多模式融合的综合应用的临床教学转变, 以实习护生为主体, 以问题为导向, 以病例为基础, 以中医临床思维为主线, 以疾病相关知识为支撑, 以师生、护患互动为手段, 形成“三轨”联合教学模式, 从而构建一种新型的中西医结合护理临床教学查房模式, 为全面提升护理工作质量、教学质量及患者满意度, 探索培养高素质综合型中医护理人才提供理论及实践依据。)